LOWER LEG DEFORMITY CORRECTION USING ILIZAROV DEVICE IN DR SOETOMO GENERAL HOSPITAL SURABAYA: A CASE SERIES - Jeffry Andrianus; Citra Ahdi Prasetya (Journal Orthopaedi and Traumatology Surabaya, 2018)
Background: limb deformity, especially lower leg deformity is a common case in orthopaedic practice. Limb deformity can be classified according to cause (Congenital, developmental, post trauma), geometry (angulation, rotation, shortening), severity and progression. In severe and complex deformity, the treatment choice is gradual correction using Ilizarov system. Benefit of the gradual correction using Ilizarov system are: (1) reduce the risk of neurovascular injury, (2) minimal soft tissue disturbance, (3) multiplanar and multidirectional correction.Cases: We have performed 11 deformity correction using ilizarov device during january 2013- September 2017. Evaluation data was obtained retrospectively from medical record. Nine patients were managed by Ilizarov device for bone lengthening indication and 2 patients for bone transport indication. The treatment result was evaluated using ASAMI scoring system for bone condition and functional condition.Results: Elevent patients were managed by Ilizarov system for gradual deformity correction. Nine patients already finished the treatment and the frame was removed. We cannot evaluate two patients because the correction was not finished. The ilizarov device was changed with other fixation because implant failure during correction phase. Evaluation using ASAMI score showed good bone score result for 9 patients and 7 excellent results for functional score.Conclusion: Ilizarov system has a promising result to correct lower limb deformity patients in Dr Soetomo General Hospital.